الزمان في ديوان (امرؤ القيس): قراءة موضوعية: Time in the Diwan of Imru' al-Qais: A Thematic Analysis - Abdulnabi Abdulmajeed, Mariam (SIBAWAYH Arabic Language and Education, 2024)
جاء الزمان في شعر امرؤ القيس عبر مدى خاص للتعريف بهواجس يخضع الشاعر فيها لجبروته، حيث يتمثّل الصراع الذي يحتويه في صلاته مع الكون والآخرين، وكان النص يؤطّر رؤية الشاعر للصلات المختلفة في البيئة الجاهلية وما تضمه من أفعال ومفاهيم، حيث يرسم عبر استعماله للزمان وتداعياته ما تتأطر به هذه العلاقات في سيرورته التي تشتمل على تجارب وآثار، وجدنا مظاهرها وتجلياتها في ديوانه الذي يصف رؤى الشاعر حينما تتحرك مع حركة الزمن، وتُشكّل فيه تلاحمه أو تنافره مع أبعاد وردت تمظهراتها في شعره الذي تبدى سجلا لعاطفته، وفكره.The passage discusses the concept of time in the poetry of Imru' al-Qais، highlighting how the poet uses time as a medium to express his anxieties and confront the forces he feels subjected to. The text frames the poet's vision of various relationships within the pre-Islamic environment، capturing the actions and concepts of that time. Through his use of time and its implications، Imru' al-Qais portrays the nature of these relationships، which encompass experiences and their impacts. The manifestations of these ideas are found in his poetry، where his reflections on time shape his emotional and intellectual responses، revealing either harmony or conflict with the dimensions that appear in his work، which serves as a record of his emotions and thoughts.Keywords: Imru' al-Qais، Diwan of Imru' al-Qais، Pre-Islamic Mu'allaqat